The story of three letters. Spiritual relay of the generations. V. N. Karazin – E. I. Koltunovsky – M. F. Sumtsov - Khirina, Ganna; Savchenko, Aliona (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2022)
Goal: based on private letters of V.N.Karazin to E.I. Koltunovsky, published by M.F. Sumtsov, supplement the biography of M.F. Sumtsov, investigate his origin, influence on the formation of his scientific views E.I. Koltunovsky, supplement the biography of V.N. Karazin with little-known facts of the latter year of his life in Kharkov, to introduce the reader to the figure of the talented artist E. I. Koltunovsky, once famous in Kharkov, the author of the only portrait of V. N. Karazin in his old age.Research methodology: the principles of historicism and objectivity, embodied by the application of special historical methods - chronological and retrospective.Scientific novelty.For the first time, information about the family of M. F. Sumtsov's mother is published, the family and scientific connections of M. F. Sumtsov with E. I. Koltunovsky are investigated, the biography of V. N. Karazin is supplemented with the facts of the last year of his stay in Kharkov, brief information about of the talented icon painter E. I. Koltunovskyi and his contribution to the creation of the cultural face of Kharkiv, traced the spiritual relay of generations of cultural figures who were closely associated with Kharkiv University.Topicality.Creating and supplementing the scientific biography of outstanding figures of culture, science and art is always an important topic of historical research. In 2023, V.N. Karazin Kharkiv National University and the Ukrainian scientific community will celebrate the 250th anniversary of the birth of the university's founder Vasyl Nazarovych Karazin. Therefore, supplementing the scientific biography of a scientist with new facts is an interesting and relevant topic. It is interesting to trace the spiritual relay between representatives of three generations of Kharkiv cultural figures.Conclusions. The little-known pages of the biographies of the founder of Kharkiv University V. N. Karazin, academician, professor of Kharkiv University, founder and first director of the Kharkiv Historical Museum M. F. Sumtsov and famous Ukrainian icon painter E. I. Koltunovskyi were studied. The authors studied the issue of scientific and personal connections between Karazin and Koltunovsky and between Koltunovsky and Sumtsov, which made it possible to trace the spiritual relay of different generations of these figures of Ukrainian culture and science. On the basis of three letters from Karazin to Koltunovsky, which were introduced into scientific circulation by M. F. Sumtsov, it was possible to reproduce some facts of the last year of the life of the founder of Kharkiv University, and a little-known portrait of Karazin in his old age, painted by Koltunovsky during the events in question, was also researched language in letters. As a result of the research, new facts were established about Sumtsov's origin, his belonging to the ancient noble family of the Koltunovskys. The continuation of the search and processing of new materials related to the biography of M.F. Sumtsov will reveal the scientific potential of this person even more fully, and will complement his contribution to the cultural development of Slobozhanshchyna.